Dynamics of the plasma column of a capillary discharge soft x-ray laser - Rocca, Jorge J., author; Tomasel, F. G., author; Shlyaptsev, V. N., author; IEEE, publisher (Colorado State University. Libraries, 1996)
A sequence of time-resolved soft X-ray pinhole images shows the rapid plasma compression in a fast high-power capillary discharge. The compressed plasma column has a length-to-diameter ratio >500 and a good axial uniformity, characteristics that have allowed for the first demonstration of large soft X-ray amplification in a discharge-created plasma.